1989
DOI: 10.1007/bf00300237
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of topoisomerases by fredericamycin A

Abstract: Fredericamycin is an antibiotic product of Streptomyces griseus that exhibits modest antitumor activity in vivo and in vitro. Because of its unique structure and the absence of a clearly defined mechanism of action, we examined the effects of this compound on L1210 cells in culture as well as on several enzymes that bind to DNA. Fredericamycin exhibits an IC50 of 4.4 microM toward L1210 cells, and its cytotoxicity is a function of the time of exposure as well as drug dose. No DNA breakage was observed in L1210… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Other successful antitumour drugs take advantage of the inhibition of topoisomerases, key enzymes in DNA transcription and replication. Fredericamycin A (FMA), an antibiotic product of Streptomyces griseus, camptothecin, an alkaloid derived from the plant Camptotheca acuminate and etoposide, a derivative of the podophyllotoxin from Podophyllum peltatum are among the antitumour drugs known to induce apoptosis in mammalian cells due to the inhibition of topoisomerases [82][83][84][85][86]. Although the induction of apoptosis in yeast cells by those drugs is not supported by the available data, some lines of evidence do support a link.…”
Section: Cytotoxicity Of Antitumour Drugs In Yeastmentioning
confidence: 99%
“…Other successful antitumour drugs take advantage of the inhibition of topoisomerases, key enzymes in DNA transcription and replication. Fredericamycin A (FMA), an antibiotic product of Streptomyces griseus, camptothecin, an alkaloid derived from the plant Camptotheca acuminate and etoposide, a derivative of the podophyllotoxin from Podophyllum peltatum are among the antitumour drugs known to induce apoptosis in mammalian cells due to the inhibition of topoisomerases [82][83][84][85][86]. Although the induction of apoptosis in yeast cells by those drugs is not supported by the available data, some lines of evidence do support a link.…”
Section: Cytotoxicity Of Antitumour Drugs In Yeastmentioning
confidence: 99%
“…43 To explore this possibility, methyl kibdelone C ( 57 ) was incubated with topoisomerase I and supercoiled DNA (Sc DNA). Topoisomerase I relaxes supercoiled DNA by introducing single-strand DNA breaks, allowing the cleaved strand to unwind, and rejoining the DNA fragments.…”
Section: Biological Studiesmentioning
confidence: 99%
“…1) Earlier studies suggest that it can act by spontaneously forming on oxidized free radical, with subsequent electron transfer to molecular oxygen, 2) but, biological evidence supporting this hypothesis has not been shown. Lathman et al reported that FMA inhibits in vitro activity of topoisomerases I and II and DNA polymerase , 3) however, the mechanism of action of the drug in vivo is obscure.…”
mentioning
confidence: 98%